2021
DOI: 10.1021/acsanm.0c03356
|View full text |Cite
|
Sign up to set email alerts
|

Specific Loading and In Vitro Controlled Release of a Ru-Based Hydrophobically Encapsulated Model Anticancer Drug inside Nanoassemblies toward Stimuli-Responsive Drug Delivery

Abstract: Stimuli-responsive water-dispersible and structurally robust nanoassemblies find tremendous importance in the biomedical domain for delivery of therapeutically active hydrophobic drugs and bioimaging applications. Herein we have demonstrated the loading of a hydrophobic model anticancer drug, [(p-cymene)Ru(curcuminato)-Cl] (Ru-Cur), inside hydrophobic compartments of different nanoassemblies, namely, micelles, liposomes, and coacervate nanodroplets, and studied the in vitro pH-and temperature-dependent control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…The mean size and the zeta potential of ATP NDs are estimated to be 270.5 ± 3.4 nm and +12.0 ± 0.5 mV, respectively. 34 It has been observed that simple ATP NDs without the embedded CDs failed to initiate any detectable spectral changes, suggesting the essential role of CDs to drive these redox conversions (Figure S24). Moreover, it has been observed that a simple binary mixture of CDs and PDADMAC at lower concentration of the polyelectrolyte, which lacks any spherical NDs, could not drive the catalytic conversion of 4-NP to 4-AP in the presence of excess NaBH 4 (Figure S25).…”
Section: Catalytic Conversion Of Nitroarenes To Arylaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean size and the zeta potential of ATP NDs are estimated to be 270.5 ± 3.4 nm and +12.0 ± 0.5 mV, respectively. 34 It has been observed that simple ATP NDs without the embedded CDs failed to initiate any detectable spectral changes, suggesting the essential role of CDs to drive these redox conversions (Figure S24). Moreover, it has been observed that a simple binary mixture of CDs and PDADMAC at lower concentration of the polyelectrolyte, which lacks any spherical NDs, could not drive the catalytic conversion of 4-NP to 4-AP in the presence of excess NaBH 4 (Figure S25).…”
Section: Catalytic Conversion Of Nitroarenes To Arylaminesmentioning
confidence: 99%
“…Earlier, we showed that the individual CDs retain their unique photoluminescence (PL) inside the NDs, which is stable over a period of 7 days. 33,34 In the present study, we have utilized the unique physicochemical and optoelectronic properties of these metal-free CD-embedded NDs to drive redox hydrogenation and visible light-induced photocatalytic reactions. The selective hydrogenation of nitroarenes to their corresponding amines by excess sodium borohydride (NaBH 4 ) in the presence of nanocatalysts is one of the most well-studied and important model catalytic reactions, which is widely applicable to the synthesis of various intermediates for amine-containing biologically active compounds, pharmaceuticals, agrochemicals, dyes, and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[46] Researchers have sought to solve this problem by developing nanoparticle systems that both shield the drug from clearance and degradation and deliver it to its cellular target. [47,48] Early efforts focused on synthesizing nanoparticles in solution to encapsulate the drug in the interior of the particle, or by noncovalently passivating the drug on the nanoparticle's surface. [46,49,50] Although these methods successfully shielded cargo from degradation and rapid clearance, they also suffered from off-target effects due to premature cargo release and low efficacy stemming from inefficient target site accumulation.…”
Section: Small Molecule Drug Attachmentmentioning
confidence: 99%
“…Over the past few years, as impacted by the surface effect, volume effect, quantum size effect, and macroscopic quantum tunneling effect, nanomaterials have been extensively employed in the modification of the AF to enhance the interface properties between the AF and matrix. At present, considerable studies are focusing on the grafting of nanoparticles, nanotubes, nanosheets, and other nanocomponents to the surface of the AF to prepare multiscale reinforcement, thereby more effectively improving the interface bonding between fiber and resin. In particular, graphene oxide (GO) nanosheets have been effective in modifying fibers to enhance the performance of the interface with the matrix. For instance, Jiang et al grafted GO on the carbon fiber surface by using electrochemical oxidation to improve the mechanical properties of its epoxy composite (CF/EP).…”
Section: Introductionmentioning
confidence: 99%